The predictive value of endplate morphology and pedicle screw bone quality score on screw loosening after single-level lumbar spinal fusion surgery - Jinxiang Zhan; Qipeng Wei; Weijun Guo; Zihao Liu; Shiji Chen; Qingyan Huang; Dongling Cai (Journal of Orthopaedic Surgery and Research)
Abstract Objective This study aims to explore the predictive value of endplate morphology and pedicle screw bone quality score on screw loosening after single-level lumbar spinal fusion surgery. Methods A retrospective analysis was conducted on the clinical data of 207 patients who underwent single-level lumbar spinal fusion (34 in the screw loosening group and 173 in the non-screw loosening group). Univariate analysis and binary logistic regression model analysis were performed using SPSS 27.0. MedCalc 23 was used to plot the receiver operating characteristic (ROC) curve to evaluate diagnostic efficacy. Results Through comparative analysis of clinical data, we found statistically significant differences between the two groups in terms of endplate morphology, lumbar CT values, and PBQ scores(P<0.05). The results of the binary logistic regression analysis indicated that endplate morphology (OR = 17.088, 95% CI: 3.886–75.142; p < 0.001) and PBQ score (OR = 3.347, 95% CI: 1.473–7.603; p = 0.004) are independent risk factors for screw loosening after single-level lumbar spinal fusion surgery. The ROC analysis showed that the area under the curve (AUC) for endplate morphology was 0.731 (95% confidence interval [CI]: 0.665–0.790), with the optimal threshold representing irregular endplate morphology (sensitivity: 94.1%, specificity: 52.0%). The AUC for the PBQ score was 0.791 (95% CI: 0.729–0.844), with an optimal threshold of 3.198 (sensitivity: 91.2%, specificity: 61.8%). Furthermore, the predictive model constructed using both endplate morphology and PBQ score had an AUC of 0.870 (95% confidence interval: 0.817–0.913), with a maximum Youden index of 0.668, yielding a diagnostic sensitivity of 88.2% and specificity of 78.6%. Conclusion Endplate morphology and pedicle screw bone quality score have significant reference value for diagnosing screw loosening after single-level lumbar spinal fusion surgery.